Foreword - Viegas, Catarina (Rei Cretariae Romanae Fautorum Acta, 2023)
The Rei Cretariae Romanae Fautores is an international learned society that brings together researchers from the territory that once belonged to the Roman Empire and from far beyond, united in the goal of developing Roman ceramics studies at its most diverse categories. Founded by Howard Comfort and Elisabeth Ettlinger in 1957, its members keep the original spirit of the association alive, convinced of the vital importance of ceramics studies to the interpretation of the societies and economies of the ancient Roman world, across its different regions and provinces.